ANALYSIS OF FACTORS INFLUENCING THE AUDIT QUALITY PUBLIC ACCOUNTING FIRM ON THE PRESENT TIME (EMPIRICAL STUDY ON ACCOUNTING PUBLIC IN PEKANBARU CITY) - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2026)
The purpose of this research is to know the effect of auditor competence. Independence of auditors. Corresponding with professional auditor services. Experience the auditor and application of audit ethics on the quality of the audit in Public Reaction of Public Realk Agencuation R1. Sample technique on This research is determined to use saturated sampling methods with the number of samples 31 percent respondents. Methods of data analysis used for testing the hypothesis is a multiple linear regression analysis method which is in test with Using the SPSS version 21. From this research it is concluded that Independent variables or independent variables in this research are auditor competence. Independence of auditors. according to professional auditor services. Auditor experience. and the application of auditors ethics simultaneously Positive positively of dependent variables or related variables is the quality of public audit office account. But if the Partial variables independent not take effect against the dependent variable.